(untitled) (e-Review of Tourism Research, 2018)
The internet has increased the percentage of consumers who consult online travel reviews before making hotel reservations. Negative messages have a strong effect on tourists’ willingness to reserve accommodations. This research aims to examine and to analyze the content of negative online customer comments from Booking.com focusing on four-star hotels in Pattaya, developing recommendations for hotel managers to develop their performance. One thousand three hundred and fifty negative comments about four-star hotels from Booking.com were selected. Seven categories of customer complaints are developed about hotel service, which are complaints about the staff, rooms, bathrooms, breakfast, facilities, location, and parking, sequentially. Suggestions concerning the response of practitioners to customer complaints are provided to improve service to reduce the number of complaints.